(untitled) (Hungarian Journal of Industry and Chemistry, 2011)
The Tire Pressure Monitoring System (TPMS) is considered to be a widespread system in automotive industry. It has two basic aspects of view – direct and indirect. The first one uses pressure sensors while the second one uses the wheel speed signals of the ESP system on board to make an estimation of the pressure levels of the tyres. The aim of this study is to find an indirect method which can be the competitor in digital signal processing of the most common and currently used Fourier-transform, and can be a match for the classic solution in complexity, necessary runtime and efficiency. Another part of this research is to find an appropriate model to generate wheel speed signals that contain the additional information to detect the pressure change, moreover to develop a function library for the research to support the measurements and to analyze the results.